2021
DOI: 10.1111/cas.15141
|View full text |Cite
|
Sign up to set email alerts
|

Lomustine and nimustine exert efficient antitumor effects against glioblastoma models with acquired temozolomide resistance

Abstract: Glioblastomas (GBM) often acquire resistance against temozolomide (TMZ) after continuous treatment and recur as TMZ-resistant GBM (TMZ-R-GBM). Lomustine (CCNU) and nimustine (ACNU), which were previously used as standard therapeutic agents against GBM before TMZ, have occasionally been used for the salvage therapy of TMZ-R-GBM; however, their efficacy has not yet been thoroughly examined. Therefore, we investigated the antitumor effects of CCNU and ACNU against TMZ-R-GBM. As a model of TMZ-R-GBM, TMZ resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…As a result of its lipo-solubility, it easily crosses the BBB, making it a viable candidate for treating intrinsic brain cancers [38,40].…”
Section: Chemotherapy: Temozolomide (Tmz)mentioning
confidence: 99%
“…As a result of its lipo-solubility, it easily crosses the BBB, making it a viable candidate for treating intrinsic brain cancers [38,40].…”
Section: Chemotherapy: Temozolomide (Tmz)mentioning
confidence: 99%
“…Nitrosourea chemotherapeutic drugs have been applied for the treatment of gliomas before the emergence of TMZ ( 81 ). Over the past decade, previous studies have shown that nitrosourea chemotherapy can be used for the remedial treatment of TMZ resistance ( 85 ).…”
Section: Nitrosourea-based Chemotherapymentioning
confidence: 99%
“…As alkylating agents with broad-spectrum antitumour activity, nitrosourea drugs may penetrate the BBB due to their nonionic properties and high lipid solubility. Nitrosourea drugs alkylate tumour cell DNA at multiple sites, inducing the formation of DNA crosslinking and the occurrence of single-strand or double-strand breaks, inhibiting DNA repair and ultimately altering the structure of DNA and proteins ( 61 , 62 ). Various miRNAs have been reported to be related to nitrosourea resistance in gliomas ( Table III ).…”
Section: Mirnas and Glioma Drug Resistancementioning
confidence: 99%